2015
DOI: 10.1016/j.actbio.2014.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cartilage or endochondral bone: A comparison of different naturally derived hydrogels

Abstract: Cartilaginous tissues engineered using mesenchymal stem cells (MSCs) have been shown to generate bone in vivo by executing an endochondral program. This may hinder the use of MSCs for articular cartilage regeneration, but opens the possibility of using engineered cartilaginous tissues for large bone defect repair. Hydrogels may be an attractive tool in the scaling-up of such tissue engineered grafts for endochondral bone regeneration. In this study, we compared the capacity of different naturally derived hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 54 publications
1
84
0
Order By: Relevance
“…It is well established that alginate hydrogels can support robust chondrogenesis [20,21] , with the incorporation of RGD peptides having previously been shown to lead to enhanced osteogenesis when this biomaterial is used for bone tissue engineering applications [15,17] . Furthermore, we chose to use a gamma-irradiated alginate as the relatively slow degradation rate of this hydrogel in its non-modified form has previously been shown to impede endochondral bone regeneration [22] .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that alginate hydrogels can support robust chondrogenesis [20,21] , with the incorporation of RGD peptides having previously been shown to lead to enhanced osteogenesis when this biomaterial is used for bone tissue engineering applications [15,17] . Furthermore, we chose to use a gamma-irradiated alginate as the relatively slow degradation rate of this hydrogel in its non-modified form has previously been shown to impede endochondral bone regeneration [22] .…”
Section: Discussionmentioning
confidence: 99%
“…After 20 days, 65% weight remained in the 100% HA but only 1% weight remained in the 100% FB. The degradation for combination hydrogels were as follows: 1, 1, 3, 11, 25, 33, 42, 50, and 50% of the weight remained for 10,20,30,40,50,60,70,80, and 90% HA, respectively. Degradation study did not include cells, and therefore no enzymatic degradation occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that fibrin had the least sGAG formation compared to the other groups. 50 As HA was added to the constructs, very little to no evidence of sGAG formation was observed at the lower ranges of HA. This could be contributed by the higher levels of FB.…”
Section: Discussionmentioning
confidence: 97%
“…For example in the case of bone marrow mesenchymal stem cells (BMSCs) encapsulated in fibrin the results confirm a diminished chondrogenic potential [37]. At the moment, this subject is still studied.…”
Section: Biomaterials In Cartilage Tissue Engineeringmentioning
confidence: 90%